Evaluation of plasma miRNA107 in Egyptian hypertensive patients - Ayat K.A. Esmail; Seham M.S. El Nakeeb; Fatma M. El-Senosy; Areej M.R. Mohammad; Rasha E.M.A. El Aziz (Al-Azhar Assiut Medical Journal)
Background and Aim Hypertension (HTN) is a polygenic disease regulated by more than 120 genes. MicroRNAs (miRNAs) have been implicated in many physiological processes like proliferation and apoptosis of cells or stress response. MiRNA107 is an intronic part of the Pantothenate kinase 1 gene (PANK1 gene), and it has several mechanisms for regulating many cardiac functions. It was involved in many pathways in the pathogenesis of HTN, atherosclerosis, heart failure, and myocardial infarction. We aimed in this study to assess the level of circulating miRNA107 in the plasma of Egyptian hypertensive patients as a potential diagnostic and predictive biomarker for HTN and its severity. Patients and methods This case–control study was conducted on 50 participants classified into: group I, 30 hypertensive patients, divided into two subgroups: group I-A (15 patients with severe HTN), group I-B (15 patients with mild and moderate HTN), and group II, 20 without HTN as a control group. Blood samples were collected for lipid profile and quantification of plasma miRNA107 by real-time PCR. Results Plasma miRNA107 was significantly decreased in hypertensive patients compared to control (P<0.001) with the best cut-off point less than 1.32488. There was also a significant difference between the control and each subgroup of HTN (P<0.001). There is a negative correlation for miRNA107 with blood pressure, low-density lipoprotein, total cholesterol, and heart failure. Conclusion MiRNA107 could be a good potential diagnostic biomarker for HTN, predict the severity of HTN and could be a therapeutic target for the treatment of HTN.